Author Meets Reader Session: 'Not the Marrying Kind' - Barker, Nicola; Monk, Daniel (feminists@law, 2013)
This is an audio recording of an author meets reader session held at the SLSA Annual Conference, University of York, 27 March 2013.  Nicola Barker's book, Not the Marrying Kind: A Feminist Critique of Same-Sex Marriage, was the winner of the 2013 Hart SLSA Book Prize. In the session she introduces the book and then engages in discussion about it with Daniel Monk.